2023
DOI: 10.3390/app13158937
|View full text |Cite
|
Sign up to set email alerts
|

Structural Failures of Adobe Buildings during the February 2023 Kahramanmaraş (Türkiye) Earthquakes

Abstract: Türkiye experienced great destruction during the Kahramanmaraş earthquake couple which occurred as Pazarcık (Mw = 7.7) and Elbistan (Mw = 7.6) on 6 February 2023. The weak structural characteristics and the magnitude of the earthquakes caused more than 50,000 casualties. Significant damage occurred in both urban and rural building stock in 11 different provinces that were primarily affected by the earthquakes. The dominant building stock is masonry structures in the rural areas of the earthquake region. Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…As a result of the earthquakes, the most structural destruction and loss of life occurred in the Hatay, Kahramanmaraş, and Adıyaman provinces. Particularly in rural areas, masonry structures, which are the dominant building stock, reinforced concrete structures, which are the dominant city building stock, mosques and minarets, transportation, and infrastructure facilities have suffered huge demolitions, and as a result, huge economic losses have occurred [45][46][47]. The destruction caused these earthquakes to be recorded as the most devastating earthquakes in the country.…”
Section: Kahramanmaraş Earthquakes On 6 February 2023mentioning
confidence: 99%
“…As a result of the earthquakes, the most structural destruction and loss of life occurred in the Hatay, Kahramanmaraş, and Adıyaman provinces. Particularly in rural areas, masonry structures, which are the dominant building stock, reinforced concrete structures, which are the dominant city building stock, mosques and minarets, transportation, and infrastructure facilities have suffered huge demolitions, and as a result, huge economic losses have occurred [45][46][47]. The destruction caused these earthquakes to be recorded as the most devastating earthquakes in the country.…”
Section: Kahramanmaraş Earthquakes On 6 February 2023mentioning
confidence: 99%
“…Previous studies conducted in earthquake zones have documented the use of cheap workmanship and poor-quality materials [61]. Such investigations have shown that the earthquake regulations in these zones were not followed [62,63].…”
Section: Other Types Of Damage In Buildings Heavily and Moderately Da...mentioning
confidence: 99%
“…The successive occurrence of earthquakes caused an increase in the loss of both lives and property. More than 500,000 structures suffered structural damage at different levels, while more than 50,000 people died [14]. Both earthquakes significantly affected 11 different provinces, such as Hatay, Kahramanmaras, Adıyaman, Malatya, Adana, Osmaniye, Kilis, Sanlıurfa, Gaziantep, Osmaniye, and Diyarbakır [14].…”
Section: Introductionmentioning
confidence: 99%